IMPROVING THE METHODOLOGICAL COMPETENCY OF FUTURE TECHNOLOGICAL EDUCATION TEACHERS IN AN INFORMED LEARNING ENVIRONMENT (Scientific journal of the Fergana State University, 2023)
This article focuses on the systematic directions of methodological competence of future technological education teachers in the informational educational environment. The place of information communication is incomparable for each growing young generation to fully respond to the demands of the time. Taking this into account, special attention was paid to some aspects of the educational environment. Necessary recommendations and instructions for the methodical competence of future teachers of technological education have been given.